Location-based services : fundamentals and operation - Küpper, Axel (John Wiley, 2005)
Location-based Services (LBSs) are mobile services for providing information that has been created, compiled, selected or filtered under consideration of the users' current locations or those of other persons or mobile devices. Typical examples are restaurant finders, buddy trackers, navigation services or applications in the areas of mobile marketing and mobile gaming.